Fishbone Analysis of the Implementation of Adolescent Reproductive Health Programs at Nagrak Public Health Center - Syafriyanti, Willyana; Widiasmara, Mira; Tania Fidzikri, Nanda Berliana (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Adolescent pregnancy has become an increasing concern in the working area of Nagrak Public Health Center, Bandung Regency, over the past three years. In response, a reproductive health program targeting adolescents has been implemented; however, its effectiveness remains suboptimal. 0Objective: This study aims to analyze the root causes of the less-than-optimal implementation of adolescent reproductive health programs at the Nagrak Public Health Center and propose actionable solutions. Method: A qualitative research method with a case study design was employed, conducted between April and May 2025. Data were analyzed using a fishbone diagram to identify contributing factors. Result and Discussion: The findings reveal several challenges: under the "man" factor, adolescents lack sufficient knowledge, parental involvement is limited, and there is a shortage of trained healthcare workers. The "material" factor points to the absence of standard operating procedures (SOPs) for adolescent reproductive health services. Under the "method" factor, activities such as youth Posyandu and counseling sessions are not routinely conducted, and existing educational media are unengaging. Lastly, the "environment" factor highlights minimal support from schools and communities. Conclusion: To optimize the program, efforts must focus on enhancing adolescent access to information and services, strengthening parental and environmental roles, and improving the quality and availability of reproductive health resources at the public health center